Genetic basis of transmission of bla NDM-1 among foodborne Vibrio parahaemolyticus strains in China - Dan Chen; Ruanyang Sun; Jing Wang; Kaichao Chen; Miaomiao Xie; Qinlu Lin; Jinwang Li; Sheng Chen; Xiaobo Liu (Applied Microbiology and Biotechnology)
Abstract Carbapenem-resistant Vibrio parahaemolyticus has emerged and spread extensively in China, posing a substantial threat to food safety and human health. This study investigated the prevalence of carbapenem resistance in V. parahaemolyticus strains recovered from various types of food samples in China, and the underlying mechanisms of transmission of the bla NDM-1 gene harbored by such strains. In this work, a total of 230 (62.1%) strains were isolated from seafood samples collected in Changsha, Hunan Province; among them, 47 strains were found to be cefotaxime-resistant. These strains were subjected to whole-genome sequencing and found to exhibit significant genetic diversity; among them, 13 strains were found to carry the bla NDM-1 gene. Nanopore sequencing showed that the bla NDM-1 gene was located in the chromosome in strain VP288 but was plasmid-borne in the other 12 strains. All bla NDM-1-bearing plasmids were of the IncC type that harbored a conserved backbone. However, the multidrug resistance regions differed significantly from each other and could be classified into four groups: (1) the plasmid pVP181-NDM was the longest and carried an additional Tn7 transposase gene; (2) both pVP156-NDM and pVP209-NDM contained two structurally different resistance regions; (3) both pVP205-NDM and pVP148-NDM harbored two bla NDM genes flanked by three copies of ISCR1 insertion elements; (4) the plasmids pVP228-NDM and pVP14-NDM contained an MDR region similar to that of pVP181-NDM. The high-level carbapenem resistance phenotype exhibited by foodborne V. parahaemolyticus underscores an urgent need for the development of effective control strategies and surveillance to limit the spread of the carbapenem resistance determinants carried by these strains. Key points • The rate of resistance of food-borne V. parahaemolyticus strains to carbapenems was at a concerning level. • The bla NDM-1 gene was located in IncC-type plasmids which shared a conserved backbone. • The MDR profiles of bla NDM-1 -bearing plasmids varied significantly.